Pedagogies and practices of disaffection: Film programmes in arts schools in a time of revolution. (1st December 2017) - Mistry, Jyoti; Andrew, David
This article offers a set of interrogative questions about the role of arts schools at the time of political change. It is significant for institutions on the African continent and in the global South to create an interventionist space that might provide an enabling environment that is both reflective and reflexive of knowledge production. By potentially positioning artistic research as a mode of pedagogy and practice (in the arts school generally) and by recognizing its implications for film programmes, this article sets out to scrutinize the changing role of the arts school. The focus in this article is on the general historical relationship between arts schools and film schools as institutional frameworks where specific pedagogic practices take place. More specifically, this scrutinization of the arts school in the global South takes place from the vantage point of Johannesburg, South Africa with a view of expressing the potential of artistic research as a potentially decolonizing approach to curriculum transformation.